Blood Redox Status of Elite Female Athletes after Table Tennis Exercise - Kabasakalis Αθανάσιος; Mougios Βασίλης (Inquiries in Physical Education and Sport, 2009)
Table tennis is a popular sport and a pleasant type of exercise. Exercise affects the redox status of the body. The aim of the present study was to investigate the effect of table tennis exercise on blood redox status markers in female athletes. Ten elite female athletes, aged 16.1 ± 1.9 years, exercised in couples for 20 min. Exercise included the execution, at maximal possible intensity, of offensive movement (forehand spin) by one athlete and block (forehand) by the other, with roles alternating every three points. Before exercise, immediately post-exercise and one hour post-exercise, the athletes provided venous blood samples for full blood count and determination of lactate, creatine kinase, as well as the markers of redox status, glutathione, urate, bilirubin, 8-hydroxy-2΄- deoxyguanosine, malondialdehyde, and protein carbonyls. Exercise induced hemoconcentration, leukocytosis, and increase of lactate. Reduced glutathione did not change significantly, while urate and bilirubin changed significantly, with an increase immediately post-exercise and a decrease one hour post-exercise. Although no significant change was found in 8-hydroxy-2΄-deoxyguanosine or protein carbonyls, malondialdehyde changed significantly, with an increase immediately post-exercise and a decrease one hour post-exercise. We conclude that, although the particular type of table tennis exercise caused exercise-induced stress, it did not induce prolonged changes on blood redox status markers of elite female athletes.